Marine transportation-technological systems safety and development (Academic journal Industrial Machine Building Civil Engineering, 2018)
The article deals with marine hydraulic structures design and operation, considering the influence of various superstructures and reloading equipment. The analysis of seismic resistance of the hydraulic structures erected in the seismic regions of Ukraine has shown that the actual seismic loads on the structures significantly exceed the design loads being determined by regulatory documents prior to 2006. In the era of globalization, transformation of cargo flows, changes in their structure, the issue of ports planning development, implying port capacities balanced development, namely: sea zone port zone, and land zone development, becomes particularly important. The design of hydrotechnical structures should be carried considering the transshipment complexes at the quay with proper scientific support.
Keywords: hydrotechnical structures; reloading equipment; seismic; ice and wave loads